Zmiany w sektorze przetwórstwa rolno-spożywczego w Polsce - Pawlewicz, Adam; Brodziński, Zbigniew (Changes in Agro-Processing Sector in Poland, 2006)
The aim of this paper is to present changes in agro-processing sector a few years before and after Polish integration with UE.The abolition of trade barriers with EU countries in 2004 forced the acceleration of adjustment processes to standards and private activity running condition in common market. It caused the profitable animation in agri-food industry, what showed basic indicators of this sector development analysis. The increase of production sale was observed with simultaneous employment decrease. The decrease of firms number is observed with simultaneous increase of average level of employment in remaining enterprises of analyzed sector. The significant investment animation is also a positive occurrence. The most important effect of integration with European Union is the increase of export and surplus in abroad trade of agri-food products.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 212-218